Faktor-Faktor yang Mempengaruhi Minat Berwirausaha (Studi Pada Karyawan Generasi Z) - Kramadibrata, Budi; Susanto, Andi Heru (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
As an employee, of course you want a safe job position for yourself. When companies don't provide a sense of security for their job positions, it can trigger turnover. Generation Z employees are known to tend not to want to be tied to a company and be independent, job insecurity encourages them to find ways to start entrepreneurship. The large number of people who are entrepreneurs can have a positive impact on the country's development. Seeing this creates entrepreneurial intention which can be influenced by intrinsic motivation and competency. For this reason, the aim of this research is to see the influence of job insecurity, competency, intrinsic motivation on entrepreneurial intention. The research methodology is quantitative. The population is aimed at generation Z employees with a purposive sample, namely generation Z with permanent employee status and have worked for ≥ 2 years as many as 130 employees. A survey with a questionnaire was used for data collection and then the analytical method used was the Structural Equation Model (SEM). The results of this study indicate that job insecurity has a positive effect on intrinsic motivation, then it is found that competency has a positive effect on intrinsic motivation and the result finds that intrinsic motivation has a positive effect on entrepreneurial intention